Changes in the photosynthetic apparatus of plants on chosen roads in Białystok - Łaska, Grażyna (Ecological Questions, 2014)
Variation in the photosynthetic apparatus of plants, in relation to the species composition and structure of plant communities, has been studied in transects along selected roads in Białystok, characterised with various intensity of traffic. Concentrations of total chlorophyll, chlorophyll a and b and carotenoids were measured in green biomass from 3 non-forest transects and 1 forest transect localised along the main roads. The concentrations of chlorophyll in green biomass from the city transects were compared with those from two reference transects in the centre of Knyszyńska Forest, beyond direct impact of road traffic. The effect of the distance of transects from the roads (4-5 m, 14-15 m and 24-25 m) and the main groups of species making plant communities (in green biomass of trees, bushes, herbal plants and moss) was also analysed. The concentration of total chlorophyll in green biomass from non-forest transects varies from 29.8 mg/g fresh mass to 66.1 mg/g fresh mass, while it is 38.3 mg/g fresh mass from the reference transect, outside the city and beyond direct influence of road traf- fic. The analogous values of total chlorophyll concentration in green biomass from the forest transects are higher than in the green biomass from non-forest transects, both in the city (70.9 mg/g fresh mass) and from the reference transect (90.4 mg/g fresh mass). According to the results, the content of total chlorophyll in plants is correlated with the intensity of traffic and the distance from the road. Changes in the photosynthetic apparatus depend also on the vertical structure and species composition of the vegetation patches studied. Higher concentrations of chlorophyll in the plants growing in the forest transect than in those in non-forest ones in the city points to the greater role of forested areas as a biological barrier. Their biological effectiveness considerably depends on the floristic composition, so the selection of species in designing of green areas should be made taking into account the effect of seasonal changes and density of individuals per a unit area.